The Shadow Prices of Voluntary Caregiving: Using Panel Data of Well-Being to Estimate the Cost of Informal Care - Rebecca McDonald; Nattavudh Powdthavee (Institute of Labor Economics (IZA), 2018)
This paper uses the wellbeing valuation (WV) approach to estimate and monetize the wellbeing impacts of informal care provision on caregivers. Using nationally representative longitudinal data from the U.K., we address two challenging methodological issues related to the economic valuation of informal care: (i) the endogeneity of informal care; and (ii) the sensitivity of income estimates used in valuation. We address the endogeneity issue by decomposing wellbeing losses into those associated with caring for a relative who had recently suffered a serious accident and those associated with caring for a relative who had not had an accident. We use of the Fixed Effects Filtered (FEF) estimator to enable the permanent income coefficient to be estimated free from individual fixed effects bias. This estimate is used instead of the transient income effect in the calculation of shadow prices of informal care. Our estimates suggest that permanent income would have to increase by approximately 102k per year on average to just compensate for the wellbeing losses from providing informal care.
Keywords: H8; I18; I31; 330; informal care; well-being; compensation variations; permanent income; happiness; shadow prices